Pelatihan Penyusunan Soal HOTS Berbasis Kurikulum Merdeka Belajar bagi Guru MTs Kecamatan Danau Teluk Jambi - A.A Musyaffa; Siti Asiah; Umil Muhsinin; Siti Ubaidah; Sunarto Sunarto (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this community service is to improve the understanding and competence of teachers at MTs in Teluk Lake District Jambi City in compiling HOTS questions based on the independent learning curriculum. The implementation method of this community service uses participatory training, with stages of providing a pretest on the HOTS concept, providing training materials and practice in compiling HOTS questions, providing a posttest, and providing an evaluation sheet for the implementation of the training. The data analysis technique uses descriptive statistical techniques using a percentage approach and graphics in presenting data. The partners of this community service are teachers at MTs Muhammadiyah Tajurhalang Bogor. The results of this community service show that MTs in Teluk Lake District Jambi City teachers have a good conceptual understanding of HOTS questions and increased skills in compiling HOTS questions based on the Independent Learning curriculum, so that they can be practiced in every learning evaluation in the classroom.